Over a million students use our free study notes to help them with their homework
To solve simulatenous equations there are two main methods, substitution and elimintion. The first method requires the principle where if x is equal to a number, say x=2 then we can substitute this in, fo...
To maintain the equality everything that is done to one side needs to be done also to the other. First, we square both sides to get rid of the power on the right-hand side. What we get is p^2 = (x+y)/5. N...
4 + 3(2x - 5) = x + 9, 3(2x - 5) = x + 5, 6x - 15 = x + 5, 5x = 20, x = 20/5, x = 4
First of all, you want to get both of the questions equating to y as this is a common factor between the two equations. SO y=7-2x and 3x-8=y As both of the equations are equal to y, we can set them equal ...
First Multiply x by (x +4) Next multiply -3 by(x+4) Then simplify the sum : x2+4x-3x-12 Hence the answer is : x2+x-12
←
614
615
616
617
618
→
Internet Safety
Payment Security
Cyber
Essentials